Cooperativismo no Sudeste do Brasil e particularidades de uma cooperativa de agricultura urbana e agroecológica em São Paulo - Pilatti, Daniella Figuerôa (Universidade Federal de São Carlos, 2024)
It can be seen that the hegemonic model of agricultural production has not been enough to deal with the socio-environmental demands of the countryside in Brazil, highlighting a need for change in what is understood and practiced as Rural Development. Therefore, this study aimed to find out what actions family farms associated with cooperatives take to implement their businesses guided by the paradigm of Sustainable Rural Development and Agroecology. In order to achieve the research objective, it was deemed necessary to understand and analyze the productive and administrative process employed within a rural cooperation context, as well as the motivations of associated family farmers to produce in a sustainable manner. To this end, a quantitative and qualitative approach was chosen, structured through bibliographic surveys, an exploratory and analytical survey of data from the 2017 Agricultural Census, and field research in an agroecological cooperative in the state of São Paulo, where semi-structured interviews were conducted, aiming to establish an overview of the work of agricultural cooperatives in the Southeast region. Better percentages were identified in family farming establishments associated with cooperatives in terms of social development aspects, but the opposite was true when studying aspects related to environmental conservation and preservation, although there were variations between the states. Meanwhile, the study on cooperative revealed the benefits of cooperatives in environmental terms, but serious limitations in socio-economic terms, mainly due to administrative inexperience.
Cooperativism in southeastern Brazil and the particularities of an urban agriculture and agroecology cooperative in São Paulo
Keywords: Agricultura familiar; Agricultura sustentável; Preservação ambiental; Family farming; Sustainable agriculture; Environmental preservation; CIENCIAS AGRARIAS